Peran Keyakinan Dan Keterlibatan Tuhan Dalam Kehidupan Masyarakat: Studi Mini Riset Masyarakat Kabupaten Jember - Nisrina Rahiyana Nabila; Sabrina Ikhdina Nur; Septyan Dwiki; Hikmah Nur Ramadani; Fika Naylul Amelia; Badriyatul Kamila; Calista Zafira; Nafisah Azzahra; Agus Arifandi (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
Muslims establish a close relationship with Allah through prayer and dhikr, while being aware of their dependence and humility. They are grateful for the blessings and sustenance that Allah has given them, and try to eliminate tyranny and inequality. This belief is based on personal experiences and inner beliefs that reinforce their sense of connection to something greater. These moral and ethical principles guide their behavior, including respecting the views and beliefs of others. While an individual's personal beliefs may change from time to time, it is important to respect everyone's right to have their own views and beliefs. Muslims acknowledge Allah's power in creating and governing life. Despite evil, belief in God persists. Religious diversity is seen as a factor that can strengthen tolerance between people, as long as there is mutual respect. It is important to respect different religious beliefs and build positive relationships with individuals who have different religious beliefs through the holy Qur'an. The resource person also emphasized the importance of an attitude that is in harmony with faith. understand and respect the beliefs and religious views of others, while maintaining personal beliefs and maintaining good relations in society.